Is There a Crisis of Truth? - Silva, Luiz Cambraia Karat Gouvea da [UNESP]; Rodrigues, Gabriel Kenzo; Ferreira, Francisco Romulo Monte (Univ Estadual Londrina, 2023)
The present paper contains a translation of Steven Shapin's article entitled Is There a Crisis of Truth? published in the Los Angeles Review of Books in December 2019. The translation was made in contact with the author and with the editor of the aforementioned journal, Michele PridmoreBrown. Shapin kindly provided us with an appendix about the article, presenting a brief update on the theme, almost two years after its publication. Seeking the best way to present an article that deals with current issues, we bring a brief biography of the author, as well as a reflective effort on how the Truth Crisis and denialism have been conveyed and debated.
Keywords: human sciences; history of science; scientific denialism